Application of Homogenization FEM Analysis to Aluminum Honeycomb Core Filled with Polymer Foams - Burlayenko, Vyacheslav. N.; Sadowski, Tomasz (My University, 2010)
The effect of polyvinyl chloride (PVC) foam filler on elastic properties of a regular hexagonal aluminum honeycomb core is studied. The unit cell strain energy homogenization approach based on the finite element method (FEM) within ABAQUS code is applied for prediction of effective material constants of the foam-filled honeycomb core. The developed FE model is then used to observe a three-dimensional stress state over the hexagonal unit cell and, thereby, to assess the influence of the foam-filling on the distribution of the local interfacial stresses.